Pengaruh Company Size, Profitabilitas, Dan Rasio Leverage Terhadap Islamic Social Reporting Pada Perusahaan Perbankan Syariah Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023 - Zuliani, Rafiza; Nurhaliza; Zefri Maulana; Nur Kumalahayati (IAIN Langsa, 2024)
This research aims to examine the influence of company size, profitability, and Leverage ratio on Islamic Social Reporting (ISR) in Islamic banking companies listed on the Indonesia Stock Exchange from 2019 to 2023. The type of data in this research is secondary data in the form of time series. The analytical method used in this research is multiple regression analysis, T-test, F-test and coefficient of determination. The data sources in this research are financial reports, annual reports and sustainability reports of sharia banking companies listed on the Indonesia Stock Exchange (BEI) for 2019-2023. From the results of the T-test analysis, it was found that company size, profitability had a significant positive influence, while leverage had no significant influence. From the results of the simultaneous analysis, it was obtained that Fcount (8.849) > Ftable (3.294) with a significance degree of 0.000 > 0.05. This means that Ho is rejected and Ha is accepted. The conclusion is that there is a significant influence between company size, profitability and leverage together (simultaneously) on ISR disclosure. This shows that when these three variables are analyzed together, they do make a significant contribution to corporate social responsibility disclosure in ISR reports.